2018
DOI: 10.3390/catal8010023
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Mizoroki-Heck Reactions Using Fluorine-Containing Agents as the Cross-Coupling Partners

Abstract: Abstract:The Mizoroki-Heck reaction represents one of the most convenient methods for carbon-carbon double bond formation in the synthesis of small organic molecules, natural products, pharmaceuticals, agrochemicals, and functional materials. Fluorine-containing organic compounds have found wide applications in the research areas of materials and life sciences over the past several decades. The incorporation of fluorine-containing segments into the target molecules by the Mizoroki-Heck reactions is highly attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 113 publications
(265 reference statements)
0
14
0
Order By: Relevance
“…According to the mechanism of Heck reaction, alkyl iodides and alkyl bromides are preferred for this approach due to having more suitable leaving groups. 28 In this work, it has been shown that alkyl chlorides could also be used in the Heck reactions using partial amounts of silver nitrate as a modifier. Through using AgNO 3 , we could either modify the Heck reaction between 5-chloro-2-methyl-4-isothiazolin-3-one (CMI) and surface vinyl groups to raise the yield of the reaction and also produce Ag/Fe 3 O 4 @SiO 2 -IT nanocomposites as the desired nanoscale product (Scheme 1).…”
Section: Results and Discussionmentioning
confidence: 97%
“…According to the mechanism of Heck reaction, alkyl iodides and alkyl bromides are preferred for this approach due to having more suitable leaving groups. 28 In this work, it has been shown that alkyl chlorides could also be used in the Heck reactions using partial amounts of silver nitrate as a modifier. Through using AgNO 3 , we could either modify the Heck reaction between 5-chloro-2-methyl-4-isothiazolin-3-one (CMI) and surface vinyl groups to raise the yield of the reaction and also produce Ag/Fe 3 O 4 @SiO 2 -IT nanocomposites as the desired nanoscale product (Scheme 1).…”
Section: Results and Discussionmentioning
confidence: 97%
“…Generally, phosphine‐based Pd catalysts such as Pd(PPh 3 ) 4 and PdCl 2 (PPh 3 ) 2 are employed as catalyst for the Heck reaction. [ 8–10 ] However, the main drawbacks with these phosphine–Pd catalyst systems are related to the fact that most of the phosphine derived ligands are toxic, highly expensive and moisture and air sensitive. [ 11 ] To overcome these limitations, enormous efforts have been devoted to synthesize various nonphosphine‐based homogeneous catalytic systems with new types of ligands such as palladacycles, [ 12,13 ] N ‐heterocyclic carbine, [ 14 ] and pincer ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alkenyl fluorides have been reported as substrates for Heck-type reactions with insertion occurring at C B but with various caveats. [29][30][31][32][33][34][35] The first is that tri-substituted alkenyl fluorides of type 1 have not been described as substrates in Heck reactions and presumably would be poorly reactive due to the high electronegativity of the F substituent and the congested nature of the alkene. 32 Consistent with this, our lab has reported that alkenes bearing only carbon substituents with smaller groups (e.g., disubstituted vs. trisubstituted alkenes) as well as substrates that are more electron rich (e.g., alkyl vs. aryl) react faster in Heck-type reactions.…”
mentioning
confidence: 99%